Advances and Outlook of Ti3c2-Based Catalysts for Electrocatalytic Hydrogen Production: A Comprehensive Overview - Radhalayam, D (American Chemical Society, 2024)
Understanding the importance of sustainable and renewable energy sources as well as effective conversion technologies is crucial to tackling the various energy challenges we face today. Hydrogen energy has arisen as one of the most important renewable energy sources, driven by the growing global demand for energy and environmental concerns. Electrocatalysis plays a pivotal role in the advancement of a sustainable energy economy by enabling the production of efficient hydrogen production. Currently, electrochemical hydrogen energy technologies are increasingly becoming integral to our daily lives, reflecting their significance and potential for addressing energy sustainability issues. The present investigation provides a thorough analysis of the latest developments in catalysts used for electrocatalytic hydrogen production. It delves into the synthesis, properties, and catalytic mechanisms of Ti3C2 while also highlighting recent research progress made in Ti3C2-based catalysts. The synthesis of Ti3C2 MXene is explored, focusing on different selective etching methods and their effects on the structural and surface properties of the materials produced. Exploring the detailed properties of Ti3C2 MXene, such as its conductivity, surface chemistry, mechanical stability, and electrochemical properties, provides a solid foundation on which to understand its catalytic performance. Understanding the process of the Ti3C2 electrocatalytic hydrogen evolution reaction (HER) is crucial, with a focus on the importance of surface terminations and electronic structure in promoting effective hydrogen production. A comprehensive analysis of the latest developments in Ti3C2-based catalysts is provided, encompassing a wide range of material combinations. This involves the use of bare Ti3C2 with different surface terminations, Ti3C2 combined with transition metal phosphides (TMPs), transition metal chalcogenides (TMCs), metal oxides, metals, and hybrid materials that include carbonaceous components. Studies have shown that the combination of Ti3C2 and other materials leads to significant improvements in HER activity, highlighting the synergistic effects between them. These advances include advances in the overpotential, Tafel slope, stability, and overall effectiveness of catalysis. This review also highlights current challenges and suggests future perspectives for the advancement of Ti3C2-based electrocatalysts for sustainable hydrogen production. © 2024 American Chemical Society.